Finger Painting bagi Anak Autis dan Tuna Grahita - Indiarsih, Melyana (GRAB KIDS: Journal of Special Education Need, 2024)
Autistic and mentally retarded children are included in the category of children with special needs, both autistic and mentally retarded people usually have physical and mental limitations including difficulties in developing their motor skills, where these motor skills have an impact on the child's daily life. Motor skills can also influence children's emotional abilities. Therefore, it is important to provide a stimulus, such as providing finger painting activities for them, with the aim of developing skills that will affect their daily lives. Thus, this research aims to examine the effect of finger painting on autistic and mentally retarded children. Finger painting can be a solution for training children's motor skills, but of course there are classifications of children with special needs with certain groups and treatments. The method used in this research is a literature review which examines discussions from several sources such as books and journal articles. From the results of literature studies that have been reviewed from various literature, it can be concluded that finger painting can have a positive impact, including training and flexing children's muscles and practicing children's writing skills.